Response fermented goat urine by EM4 on Productivity of Brachiaria humidicola and Digitaria milanjiana - keke rejeki sembiring; nevy diana hanafi; sayed umar (Jurnal Agroekoteknologi, 2019)
Utilization of EM4 fermented goat urine as organic fertilizer that can improve productivity of Brachiaria humidicola and Digitaria milanjiana. The study was conducted in field laboratory Animal Science Study Program Faculty of Agriculture, University of Sumatera Utara in June to November 2017, using a randomized block design factorial divided into 2 factor, composed of  the type of grass (Brachiaria humidicola and Digitaria milanjiana) and the fertilizer dose (0, 100, 150, 200, 250 ml / polybag). The variables observed were plant height, fresh weight production and dry matter production. The results showed that increasing dose  fermented goat urine give the very real result (P<0.01) increased plant height, fresh weight production and dry matter production and the productivity Digitaria milanjiana hed nigher Brachiaria humidicola plant height, fresh weight production and dry matter production it is concluded that increased dose fermented goat urine increased on productivity of Brachiaria humidicola and Digitaria milanjiana. Keywor/ds: fermented goat urine, Brachiaria humidicola, Digitaria milanjiana, productivity, fertilizing dose.